Calculation of natural recharge in large areas, as a function of lithology and rainfall - Sanz-Pérez, Eugenio; Menéndez-Pidal, Ignacio (Instituto Mexicano de Tecnología del Agua (IMTA), 2013)
In a region as large as Spain, annual mean recharge is shown to be a fixed proportion of the mean rainfall for each lithology. This determination is based on statistical inferences from a complete sample of 875 springs for which mean flow and catchment areas are known and which have been grouped into distinct rainfall regions. Recharge rates have thus beenestablished with respect to rainfall for six lithological groups with different permeability: sands, gravels and generally alluvial formations, 8.3%; conglomerates, 5.6%; sandstones, 7.3%; limestone and dolomite 34.3%; marls, marly limestones, silts and clays, 3.3%; and hard rocks, 1.3%. Considering the representativeness of Spain, which is large in size and hasa highly varied lithology, topography and rainfall, these recharge rates for rainfall are probably quasi-universal values that can be used to estimate average recharge or average groundwater resources of large regions in any part of the world (except in special cases such as areas with permafrost, for example). For any case, these recharge rates can be adapted to each region according to its particular characteristics. Rainfall and lithology data are very common, and so the method can be widely used to calculate hydraulic balances. En una región amplia como España se demuestra —mediante inferencias estadísticas sobre una muestra completa de 875 manantiales en los que se conoce su caudal medio y la litología de su área de alimentación y que han sido agrupados en regiones de distinta pluviometría— que la recarga media anual es una fracción fija de la precipitación media para cada litología. Se han establecido así unas tasas de recarga respecto de la precipitación para seis grupos litológicos de diferente permeabilidad: arenas, gravas y formaciones aluviales en general, 8.3%; conglomerados, 5.6%; areniscas, 7.3%; calizas y dolomías, 34.3%; margas, margocalizas, limos y arcillas, 3.3%; otras rocas, 1.3%. Teniendo en cuenta la representatividad de España, la cual tiene una gran variabilidad de litología, ...